Comparison of Attracting Investments Through ICO and IPO in International Practice - Y. Y. Ramanouski (Цифровая трансформация)
The development of new technologies in the field of finance (fintech) creates new opportunities and ways to carry out economic activity. One of these tools is blockchain and technologies created on its basis. One of the most famous of such tools is the process of issuing and selling digital coins (tokens), called Initial coin offering (ICO). The ICO process is often mistakenly viewed as a simpler and faster alternative to the classic IPO procedure. However, these procedures have more differences than similarities. This article provides a detailed comparison of IPO and ICO in terms of a number of key parameters, key similarities and differences from the point of view of both the investor and the issuer. At the end, there are recommendations for choosing an instrument depending on the goals of the investor and the issuer.